Intermediate-Dose Enoxaparin After Cardiac Ablation Procedures - Drayton A. Hammond; Christina E. DeRemer; David M. Killough; Adam E.Berman (Journal of Hypertension and Cardiology, 2014)
Objective: Ablation of foci within the atria has been shown to resolve symptoms of atrial fibrillation and atrial flutter. However, no standard has been established for anticoagulation after the procedure. Enoxaparin has been well described in the literature as a means to provide anticoagulation after ablation procedures. The only enoxaparin doses previously studied were 0.5 mg/kg and 1 mg/kg, both given every 12 hours. The purpose of the study was to compare the incidence of a major bleed or vascular complication in patients who received enoxaparin doses between 0.5 mg/kg and 1 mg/kg every 12 hours with patients who received either 0.5 mg/kg or 1 mg/kg every 12 hours. Methods: This IRB-approved, single-center, retrospective, cohort study included subjects greater than 18 years of age who received an atrial fibrillation or atrial flutter ablation procedure and at least one dose of enoxaparin post-ablation. Results: There were 119 subjects who satisfied the inclusion criteria. The primary outcome, incidence of major bleeding or vascular complication, did not demonstrate a statistically significant difference between groups (p = 0.92). The incidences were 4.8% with enoxaparin ≥ 1 mg/kg, 3% with enoxaparin between 0.5 mg/kg and 1 mg/kg, and 3.2% with enoxaparin ≤ 0.5 mg/kg. No subject experienced an ischemic stroke or transient ischemic attack within 28 days of a cardiac ablation procedure. Conclusion: Significant increases in major bleeding or vascular complications may not exist with an intermediate dose of enoxaparin provided after a cardiac ablation procedure.
Keywords: Enoxaparin